Utilizing a strait-range green phosphor γ-AlON:Mn,Mg for the task of achieving a super-broad hue gamut display - My Hanh Nguyen Thi; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
The screen backlighting produced by green β-sialon:Eu, as well as red K2SiF6:Mn phosphors, have an extremely expansive hue gamut that encompasses the majority of the national television system committee (NTSC) triangle. For our research, a substitute phosphor in green would be probed in terms of improving the screen hue range even further. The phosphor γ-AlON:Mn,Mg appears to be green in color with a smaller radiation band of colors than sharp β-silaon:Eu. By replacing γ-AlON:Mn,Mg with β-sialon:Eu, the screen hue range in the blue-green area is significantly expanded. In both the CIE 1931 and CIE 1976 hue spaces, the hue range of screens with γ-AlON:Mn,Mg, and K2SiF6:Mn entirely surpasses the NTSC benchmark. Furthermore, the stability of LEDs emit white light using γ-AlON:Mn,Mg appears to be similar to LEDs that utilize β-sialon:Eu.